HYDRO POWER PLANT PARMONANGAN - 2 A FINANCIAL FEASIBILITY STUDY - Warjo
Indonesia still depends on fossil energy sources. According to BPPT (2021), “until 2019, 90.7% of the national primary energy supply was met from coal, oil and natural gas.” If Indonesia does not use other energy sources, it will have an energy crisis in the future. Renewable energy sources are wind, sunlight and micro hydro, which are more friendly to the environment. According to Article 20 paragraph 3 of Law Number 30 of 2007 concerning Energy, “the supply of renewable energy must be increased by the Government and Regional Governments in accordance with their respective authorities.” The MiniHydro Power Plant (PLTM) is a power plant that uses hydropower such as irrigation canals, rivers or natural waterfalls. In planning a power plant, a further study on the feasibility and design of the power plant is needed. This final project conducted to determine the financial feasibility of Development PLTM Parmonangan - 2 with a capacity of 2x5 MW. In this study, the author has conducted financial feasibility study by computing Net Present Value, Internal Rate of Return, Discounted Payback Period and Sensitivity Analysis to determine the financial feasibility of developing the PLTM Parmonangan – 2. The Net Present Value for this project based on Condition 1 which is based on Normal Condition; it means the project going smooth as expected with no cost overrun and no decreasing on revenue, is Rp. 217,154,350,279 which is greater than zero, therefore the NPV is Positive. Then, based on the Sensitivity Analysis conducted based on 5 conditions that possibily occur during the construction period and during the economics lifetime of the PLTM Parmonangan – 2, it can be concluded that if there are costs overruns and/or income decreases, the NPV is still higher than zero, and the IRR is still higher than the loan interest rate. Furthermore, the Discounted Payback Period in the worst condition, which is Condition 5 - when the project cost increased by 10% include cost overrun in the construction phase and operation & maintenance cost and the revenue decreased by 10% - is only 1 year longer than normal conditions. Based on the financial feasibility study above, can be concluded that the Development of PLTM Parmonangan – 2 is financially feasible